Pathophysiology of Coagulopathy Induced by Traumatic Brain Injury Is Identical to That of Disseminated Intravascular Coagulation With Hyperfibrinolysis - Wada, Takeshi; Shiraishi, Atsushi; Gando, Satoshi; Yamakawa, Kazuma; Fujishima, Seitaro; Saitoh, Daizoh; Kushimoto, Shigeki; Ogura, Hiroshi; Abe, Toshikazu; Mayumi, Toshihiko; Sasaki, Junichi; Kotani, Joji; et al. (Frontiers in Medicine, 2021)
Background: Traumatic brain injury (TBI)-associated coagulopathy is a widely recognized risk factor for secondary brain damage and contributes to poor clinical outcomes. Various theories, including disseminated intravascular coagulation (DIC), have been proposed regarding its pathomechanisms; no consensus has been reached thus far. This study aimed to elucidate the pathophysiology of TBI-induced coagulopathy by comparing coagulofibrinolytic changes in isolated TBI (iTBI) to those in non-TBI, to determine the associated factors, and identify the clinical significance of DIC diagnosis in patients with iTBI. Methods: This secondary multicenter, prospective study assessed patients with severe trauma. iTBI was defined as Abbreviated Injury Scale (AIS) scores ≥4 in the head and neck, and ≤2 in other body parts. Non-TBI was defined as AIS scores ≥4 in single body parts other than the head and neck, and the absence of AIS scores ≥3 in any other trauma-affected parts. Specific biomarkers for thrombin and plasmin generation, anticoagulation, and fibrinolysis inhibition were measured at the presentation to the emergency department (0 hour) and 3 hours after arrival. Results: We analyzed 34 iTBI and 40 non-TBI patients. Baseline characteristics, transfusion requirements and in-hospital mortality did not significantly differ between groups. The changes in coagulation/fibrinolysis-related biomarkers were similar. Lactate levels in the iTBI group positively correlated with DIC scores (rho=-0.441, p=0.017), but not with blood pressure (rho=-0.098, p=0.614). Multiple logistic regression analyses revealed that the injury severity score was an independent predictor of DIC development in patients with iTBI (odds ratio=1.237, p=0.018). Patients with iTBI were further subdivided into two groups: DIC (n=15) and non-DIC (n=19) groups. Marked thrombin and plasmin generation were observed in all patients with iTBI, especially those with DIC. Patients with iTBI and DIC had higher requirements for massive transfusion and emergency surgery, and higher in-hospital mortality than those without DIC. Furthermore, DIC development significantly correlated with poor hospital survival; DIC scores at 0 hour were predictive of in-hospital mortality. Conclusions: Coagulofibrinolytic changes in iTBI and non-TBI patients were identical, and consistent with the pathophysiology of DIC. DIC diagnosis in the early phase of TBI is key in predicting the outcomes of severe TBI.